Chromite and Its Thin Kosmochlor and Cr-Omphacite Cortex in Amphibolite from the Myanmar Jadeite Deposits - Yu Zhang; Guanghai Shi; Jiabao Wen (Crystals)
Chromite in the amphibolites of the Myanmar jadeite deposits has not been well studied. Mineralogical studies on chromite and related kosmochlor and Cr-omphacite in the amphibolite of the Myanmar jadeite deposits were conducted. Compared to the chromite in the adjacent serpentinized peridotite, the chromite had higher Cr2O3 (45.67–54.25 wt.%) and MnO (1.82–1.90 wt.%) but lower MgO (1.00–1.96 wt.%) and Al2O3 (1.05–15.09 wt.%), similar to the published chromite compositions in jadeitite. Serpentinite was derived from a highly depleted mantle peridotite. There were at least two stages of metasomatism during the transformation of serpentinite + chromite to magnesio-katophorite + chromite + thin kosmochlor (and/or Cr-omphacite cortex). The first stage was the Ca-rich metasomatism of serpentinite, resulting in sodic-calcic amphibole (magnesio-katophorite), which preceded the formation of jadeite. The second stage of Na-rich metasomatism was produced by the Na-Al-Si-rich fluids with the magnesio-katophorite + chromite (contemporaneous with the formation of jadeite). The composition of the fluid was altered by a reaction with magnesio-katophorite, increasing the Ca-Mg content and resulting in the formation of kosmochlor rich in Ca-Mg and/or peripheral Cr-omphacite. This kosmochlor–Cr-omphacite belongs to the Jd-Kos-Di ternary join, which differs from the kosmochlor–Cr-jadeite (which belongs to the Jd-Kos join in jadeitite). The formation of jadeitite with chromite + kosmochlor + Cr-jadeite occurs when large amounts of Na-Al-Si-rich fluids have wrapped the pieces of chromite-bearing amphibolite. This also explains the proverbial “moss spray green” given that amphibole (with chromite) brings out the green color in jadeitite.